The Role and Authority of Adoptive Fathers in Marriage Guardianship: A Comparative Analysis between Islamic Family Law and Civil Law - Thoiyibi, M; Afrizal, Afrizal; Mardhiah, Ainul; Jarullah, Jarullah; Diyetmawati, Diyetmawati (Jurnal El-Thawalib, 2025)
This article examines the role and authority of the adoptive father in marriage guardianship, employing a comparative approach between Islamic law and civil law. In Islamic law, marriage guardianship is a pillar that must be fulfilled in the implementation of a marriage contract and can only be carried out by a man who has a blood relationship with the bride. In civil law, particularly as outlined in Staatsblad 1917 No. 129, children adopted through a court decision who are legally adopted obtain a legal status equal to that of biological children. This difference has implications for the validity of a marriage. This type of qualitative research uses a normative and comparative legal approach; primary data comes from the Compilation of Islamic Law (KHI), Law Number 1 of 1974 concerning Marriage, the Civil Code (KUHPerdata), and classical and modern literature in Islamic jurisprudence and secondary data comes from the results of previous research, scientific journal articles, Islamic law books, and civil law. Library research is used to collect data from legal documents and scientific literature. The data collected in this study will be analyzed using both descriptive and analytical methods, as well as comparative methods. The results of this study indicate that there are significant differences between Islamic law and civil law in their views on the role of the adoptive father as a marriage guardian. Islamic law explicitly rejects the authority of the adoptive father because there is no blood relationship, while civil law provides equal legal standing between adopted children and biological children through court ratification. This difference has implications for the validity of marriages that can be recognized by the state but not recognized according to Sharia, so it is essential to consider the harmony between the two legal systems in the practice of marriage guardianship in Indonesia